db4DNASeq: An Object-oriented DNA Database Model associated with Sequence Search Method - Ng, Keng Hoong; Shoo, Kyuk Wei; Diong, Wei Liam; Phon-Amnuaisuk, Somnuk; Ho, Chin Kuan (2008)
DNA database consists of many nucleotide sequences, it is not only supporting typical database queries, but it also needs to facilitate sequence search and alignment. In this paper, we present an object-oriented nucleotide database which is designed not only for the convenience of executing normal database operations such as insertion, modification or data querying in a fast manner, but it also supports a fast search method on database sequences with reasonable tradeoff between time and memory usage.